John Rawls: Dreptatea ca imparțialitate și dreptatea politică (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This paper examines John Rawls's conception of justice as fairness and political justice. It explains the concepts of the original position and the veil of ignorance, arguing that rational individuals would choose equal basic liberties and the difference principle as the basis of a just society. The paper also discusses Rawls's theory of political liberalism, emphasizing reasonableness, overlapping consensus, and public reason as essential principles for democratic coexistence in pluralistic societies. This abstract is generated with artificial intelligence.